Direct-methane Solid Oxide Fuel Cell (SOFC) with Ni-SDC Anode-Supported Cell - Asmida, Ideris; Croiset, Eric; Pritzker, Mark; Amin, Ashraf (Pergamon, 2017)
The performance of a Ni-SDC anode-supported cell operating with a dry CH4 feed stream and the effectiveness of exposing the anode to H2 as a method of removing carbon deposits are evaluated. This has involved the continuous monitoring of the outlet gas composition during CH4 operation and H2 exposure. A degradation rate in the cell voltage (∼1.33 mV h−1) is observed during 100 h operation with dry CH4. Carbon is detected in the Ni-SDC anode after the stability test but only in the portion of the anode closest to the fuel channel. No carbon is detected at the electrolyte-anode interface, which is the likely reason that the cell performance remains relatively stable. The information obtained from SEM and gas outlet composition analyses can be explained by a process whereby most of the CH4 that reacts decomposes into H2 and C in the Ni-SDC anode near the fuel channel. H2 then makes its way to the anode-electrolyte interface where it is electrochemically oxidized to H2O which can also react with any C that may have formed, leaving behind C primarily at the fuel channel. When an aged cell is exposed to H2, carbon-containing gases (CO, CH4 and CO2) are released, indicating that some carbon has been removed from the anode. Examination of the anode after the test shows that some carbon still remains after this treatment.